Comparison of intraoperative O-arm- and conventional fluoroscopy (C-arm)-assisted insertion of pedicle screws in the treatment of fracture of thoracic vertebrae. (18th January 2017) - Liu, Hao; Wang, Yimeng; Pi, Bin; Qian, Zhonglai; Zhu, Xiaoyu; Yang, Huilin
Purpose: To introduce the intraoperative O-arm-assisted pedicle screw insertion without any navigation system in the treatment of thoracic vertebrae fracture and compare it to conventional fluoroscopy (C-arm)-assisted pedicle screw insertion technique. Methods: About 156 pedicle screws were inserted in 23 patients (C-arm group), and 208 pedicle screws were inserted in 30 patients (O-arm group). The postoperative computed tomography images were analyzed for pedicle violation based on Gertzbein classification. The total surgery time, the average time required for inserting a screw, the mean action times of adjusting guide probe and pedicle screw, and the hospitalization time were compared in both groups, respectively. The American Spinal Injury Association (ASIA) was used for evaluating the health outcomes pre- and postoperatively. Results: There are the higher accuracy rate of satisfactory pedicle screw placement (grades 0 and 1) and the less incidence of medial perforation in the O-arm group compared to the C-arm group ( p < 0.05). The average time required for inserting a screw, the action times of adjusting the guide probe and pedicle screw, and the hospitalization time in the O-arm group are less than the respective ones in the C-arm group ( p < 0.05). There was no significant difference for the total surgery time between both groups. No further damage of the nerve function postoperatively is found according to the ASIA grade. Conclusion: The O-arm-assisted pedicle screw insertion without navigation we described provides higher accuracy of pedicle screw placement and better clinical efficacy compared to conventional fluoroscopy (C-arm) technique.